Goal programming approach to fully fuzzy fractional transportation problem. Issue 1 (11th December 2019) - Anukokila, P.; Radhakrishnan, B.
Abstract : In this paper, authors devoted to study a fully fuzzy fractional multi-objective transportation problem by using goal programming approach. Also trapezoidal membership functions are applied to each objective function and constraints to describe a each fuzzy goal. A numerical example is provided to illustrate the efficiency of the multi-objective proposed approach.